How Safe to Eat Are Raw Bivalves? Host Pathogenic and Public Health Concern Microbes within Mussels, Oysters, and Clams in Greek Markets - Athanasios Lattos (MDPI AG, 2021)
Raw-bivalves consumption is a wide trend in Mediterranean countries. Despite the unambiguous nutritional value of seafood, raw consumption of bivalves may involve risks that could pose a significant threat to consumers’ health. Their filter-feeding behavior is responsible for the potential hosting of a wide variety of microorganisms, either pathogenic for the bivalves or public health threats. Under this prism, the current study was conducted in an effort to evaluate the risk of eating raw bivalves originating from the two biggest seafood markets in Thessaloniki, the largest production area of bivalves in Greece. Both microbiological and molecular methodologies were applied in order to assess the presence of various harmful microbes, including noroviruses, Bonamia, Marteilia, Esherichia coli, Salmonella, and Vibrio. Results indicated the presence of several Vibrio strains in the analyzed samples, of which the halophilic Vibrio harveyi was verified by 16S rRNA sequencing; other than this, no enteropathogenic Vibrio spp. was detected. Furthermore, although Esherichia coli was detected in several samples, it was mostly below the European Union (EU) legislation thresholds. Interestingly, the non-target Photobacterium damselae was also detected, which is associated with both wound infections in human and aquatic animals. Regarding host pathogenic microorganisms, apart from Vibrio harveyi, the protozoan parasite Marteilia refrigens was identified in oysters, highlighting the continuous infection of this bivalve in Greece. In conclusion, bivalves can be generally characterized as a safe-to-eat raw food, hosting more bivalve pathogenic microbes than those of public health concern.